Boiling and Frying Peanuts Decreases Soluble Peanut (Arachis Hypogaea) Allergens Ara h 1 and Ara h 2 But Does Not Generate Hypoallergenic Peanuts - Comstock, Sarah S.; Maleki, Soheila J.; Teuber, Suzanne S. (PloS one, 2016)
Peanut allergy continues to be a problem in most developed countries of the world. We sought a processing method that would alter allergenic peanut proteins, such that allergen recognition by IgE from allergic individuals would be significantly reduced or eliminated. Such a method would render accidental exposures to trace amounts of peanuts safer. A combination of boiling and frying decreased recovery of Ara h 1 and Ara h 2 at their expected MWs. In contrast, treatment with high pressures under varying temperatures had no effect on protein extraction profiles. Antibodies specific for Ara h 1, Ara h 2, and Ara h 6 bound proteins extracted from raw samples but not in boiled/fried samples. However, pre-incubation of serum with boiled/fried extract removed most raw peanut-reactive IgE from solution, including IgE directed to Ara h 1 and 2. Thus, this method of processing is unlikely to generate a peanut product tolerated by peanut allergic patients. Importantly, variability in individual patients' IgE repertoires may mean that some patients' IgE would bind fewer polypeptides in the sequentially processed seed.